The Idea of Notational Ekphrasis in Words and Music - Thomas Gurke (Humanities, 2025)
This chapter will focus on the presence of musical notation in literary texts, their aesthetic, (inter-)medial presence and potentialities, in paradigmatic Modern short stories such as Katherine Mansfield’s “The Wind Blows” (1915), Virginia Woolf’s “The String Quartet” (1921) and Vladimir Nabokov’s “Music” (1932). What these stories share is a perception of music as sonorous moving forms, symbolic imagery or seemingly ‘dancing’ musical notation on the page. In introducing the term notational ekphrasis, I wish to differentiate these phenomena as overt and covert for the larger theory of intermediality. In doing so, I will show how these narratives negotiate musical notation, writing and iconicity.